Lichen Planus Pemphigoides Associated With PD-1 and PD-L1 Inhibitors: A Case Series and Review of the Literature. (2nd May 2022) - Boyle, Margaret M.; Ashi, Shaymaa; Puiu, Tudor; Reimer, Danielle; Sokumbi, Olayemi; Soltani, Keyoumars; Onajin, Oluwakemi
Abstract: Immune checkpoint inhibitors are increasingly being used in the treatment of various solid organ and hematologic malignancies. Dermatologic toxicities associated with programmed cell death protein-1 (PD-1) and programmed death ligand-1 (PD-L1) therapy have been widely reported in the literature. It is important for clinicians to be aware of these toxicities to ensure prompt recognition and treatment. Herein, we present the clinical, histopathologic, and immunofluorescence findings of 3 patients diagnosed with lichen planus pemphigoides (LPP) after treatment with anti-PD-1 inhibitors. We also reviewed the literature and summarize 7 previously reported cases of LPP associated with anti-PD-1 and anti-PD-L1 inhibitors. LPP was diagnosed at a median time of 24.4 weeks (range: 4–78 weeks) after initiation of immunotherapy. Clinical findings included papules, plaques, erosions, vesicles, and bullae on the trunk and extremities. Oral involvement was present in half the cases. Histopathologic features of immunotherapy-induced LPP included lichenoid or vacuolar interface dermatitis, the presence of eosinophils, and subepidermal bullae. Direct immunofluorescence demonstrated linear deposition of immunoglobulin G (IgG) or C3. Indirect immunofluorescence demonstrated linear IgG along basement membrane zone on monkey esophagus in 2 cases and linear IgG on the epidermal side of salt split skin in 3 cases. Serum anti-BP180 was elevated in all cases in which enzyme-linked immunosorbent assay was performed.